Sensory integration and neuromodulatory feedback facilitate Drosophila mechanonociceptive behavior - Hu, Chun; Petersen, Meike; Hoyer, Nina; Spitzweck, Bettina; Tenedini, Federico; Wang, Denan; Gruschka, Alisa; Burchardt, Lara S.; Szpotowicz, Emanuela; Schweizer, Michaela; Guntur, Ananya R.; Yang, Chung-Hui; et al. (Nature Neuroscience, 2017)
Nociception is an evolutionarily conserved mechanism to encode and process harmful environmental stimuli. Like most animals, Drosophila melanogaster larvae respond to a variety of nociceptive stimuli, including noxious touch and temperature, with stereotyped escape responses through activation of multimodal nociceptors. How behavioral responses to these different modalities are processed and integrated by the downstream network remains poorly understood. By combining trans-synaptic labeling, ultrastructural analysis, calcium imaging, optogenetics and behavioral analyses, we uncovered a circuit specific for mechanonociception but not thermonociception. Notably, integration of mechanosensory input from innocuous and nociceptive sensory neurons is required for robust mechanonociceptive responses. We further show that neurons integrating mechanosensory input facilitate primary nociceptive output by releasing short neuropeptide F, the Drosophila neuropeptide Y homolog. Our findings unveil how integration of somatosensory input and neuropeptide-mediated modulation can produce robust modality-specific escape behavior.
CRIS-Team Scopus Importer:2021-11-16